MULTIKULTURALISME DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN (KAJIAN QUR’AN DAN HADITS) - Ade Mandala; Umi Sumbulah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine multiculturalism from the perspective of the Qur’an and Hadith and how it is implemented in the world of education. This research uses library research. The results of this research show that many verses from the Qur’an and Hadith explain diversity, including race, ethnicity, nation, language, and even religion. However, this diversity is not meant to bring each other down, but rather to get to know each other's. Thus, it is clear that long before the word "multiculturalism" existed, the Qur'an and Hadith already proclaimed it. Furthermore, the three principles of multiculturalism that can be applied in the world of education are tolerance, respect for all people regardless of their background, and justice. In its implementation, several steps must be taken to ensure that the learning environment reflects and respects students' cultural, religious, ethnic, and social diversity, namely: 1. Inclusive curriculum, 2. Training for teachers and staff, 3. Promotion of intercultural experiences, 4. Use of representative learning materials, 5. Development of intercultural skills, 6. Fair and skills-based assessment, and finally support for students from various cultural backgrounds. As a result, it is hoped that understanding multiculturalism will help students become more humanist, democratic, and pluralist in their lives.